Alternative schemes for twin-field quantum key distribution with discrete-phase-randomized sources - Li, Huaicong; Zhang, Chunmei (Frontiers in Physics, 2023)
The twin-field quantum key distribution (TF-QKD) protocol and its variants can break the well-known rate-loss bound without quantum repeaters, which have attracted great attention. Generally, to ensure the security of these protocols, weak coherent states in the test mode are always assumed with continuous randomized phases. However, this assumption is difficult to satisfy well in practice. To bridge the gap between theory and practice, we propose two alternative discrete-phase-randomized (DPR) TF-QKD protocols, which remove the phase sifting procedure in the code mode. Simulation results show that, compared with previous DPR-TF-QKD protocols, our modified protocols can significantly improve the secret key rate in the low channel loss range, which is very promising for practical TF-QKD systems.